Achante et Céphise ou La sympathie pastorale héroïque en trois actes : (1751) - Rameau, Jean-Philippe 1683-1764 (Warner Classics, Erato, 2021)
Breaking a silence of nearly 270 years: an unexpected revival of Rameau's Achante et Céphise, this album is under the baton of Alexis Kossenko, with Les Chantres du CMBV and Les Ambassadeurs, starring Sabine Devieilhe, Cyrille Dubois, David Witczak, Judith van Wanroij. Jean-François Marmonte's libretto combines mythology and fairytale in a single subject, mixing the magical powers of the evil genie, Oroès, with traditional tributes to Venus and Love
Interpreten: Sabine Devieilhe (Céphise). Cyrille Dubois (Achante). David Witczak (Le Génie Oroès). Judith van Wanroij (Zirphile). Les Chantres du Centre de musique baroque de Versailles. Les Ambassadeurs - La Grande Écurie. Alexis Kossenko (Dirigent)
Aufnahme: Paris, Notre-Dame-du-Liban, 7.-11. Dezember 2020
Keywords: CD